EVALUATION OF PHOSPHATE SOLUBILIZING BACTERIA (PSB) POPULATION IN NON RHIZOSPHERE AND RHIZOSPHERE OF Gliricidia sepium, Leucaena leucochepala,AND Sesbania grandiflora PLANT ON DRY LAND IN THE RAINY SEASON - I G., Widnyana; Suarna, I W.; Lindawati, S. A. (Jurnal Peternakan Tropika; Vol 6 No 1 (2018): Vol. 6 No. 1 (2018), 2018)
This experiment aims to determine the population of phosphate solubilizing bacteria (PSB) in non-rhizosphere and rhizosphere plants on dry land in the rainy season. The experiment was conducted for 3 months including sampling at three strata system farm of Faculty of Animal Husbandry at Bukit Jimbaran; analysis of soil at Laboratory of Animal Production Technology and Microbiology Faculty of Animal Husbandry and at Soil Science Laboratory, Faculty of Agriculture, Udayana University. This experiment follows an additive linear model with the assumption that the difference only caused by the different types of plants while other factors are uniformly homogeneous. Sampling was done on four rhizosfere including; non-rhizosphere (NR), Gliricidia sepium rhizosphere (RG), Leucaena leucochepala rhizosphere (RL), and Sesbania grandiflora rhizosphere (RT) with four replications. The variables observed in this experiment including: Total PlateCount (TPC), Total phosphate solubilizing bacteria (PSB), P (phosphorus) element, and water content. The result showed that TPC soil in the range of 0,57×10 8 -5,6×10 8 cfu/g, showed no significant different to all treatment. Total phosphate solubilizing bacteria (PSB)  in range of 0,35×10 7 - 2,88×10 7 cfu/g showed no significant different to all treatments. P (phosphorus) elements, in tretment NR same withtreatment RT are range of 10,27ppm significant different with RG and RL. Water content ranged from 9,25 - 9,84 % With the result is highest in treatment RG was no significant higher than RT and markedly higher than the NR and RL. Based on the experiment it could be concluded that the population of phosphate solubilizing bacteria (PSB) in non-rhizosphere tend to is lower compared with RG, RL, and RT on dry land in the rainy season. The content of P (phosphorus) element in non-rhizosphere is same with RT but lower than RG and RL. Water content in non-rhizosphere same with RL but lower than RG and RT. Keywords: phosphate solubilizing bacteria, non rhizosphere , rhizosphere